Eksistensi dan Kontekstualisasi Konsep Jihad - Muhammad Reza Fadil (MAGHZA, 2018)
This article presents a study of the existence of jihad in the Quran by examining the letter of Al-Taubah verse 41. This verse has become one of the sources of motivation or encouragement for the Muslims from the beginning to the present to carry out jihad. In addition, this study also explains that jihad in the sense of war against the enemy physically is indeed the basic meaning of jihad itself which cannot be eliminated. In addition to the wider meaning of jihad, it is also part of its meaning. This study refutes the accusations which state that Islam, especially the Quran, teaches its adherents to commit acts of violence with the concept of jihad. Research in this study found that war is actually part of the final solution that is in effect today in international disputes and recognized by international law.